2006
DOI: 10.1016/j.neuroimage.2005.10.014
|View full text |Cite
|
Sign up to set email alerts
|

Influence of tissue conductivity anisotropy on EEG/MEG field and return current computation in a realistic head model: A simulation and visualization study using high-resolution finite element modeling

Abstract: To achieve a deeper understanding of the brain, scientists, and clinicians use electroencephalography (EEG) and magnetoencephalography (MEG) inverse methods to reconstruct sources in the cortical sheet of the human brain. The influence of structural and electrical anisotropy in both the skull and the white matter on the EEG and MEG source reconstruction is not well understood.In this paper, we report on a study of the sensitivity to tissue anisotropy of the EEG/MEG forward problem for deep and superficial neoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
469
0
18

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 405 publications
(499 citation statements)
references
References 44 publications
(78 reference statements)
12
469
0
18
Order By: Relevance
“…following transcranial direct current stimulation) along trajectories parallel to the primary direction of the fiber tracts [4,27]. Sources located deep in the brain, as well as those bordering strongly anisotropic tissue, are misrepresented in EEG localization when neglecting the effects of white matter anisotropy [4].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…following transcranial direct current stimulation) along trajectories parallel to the primary direction of the fiber tracts [4,27]. Sources located deep in the brain, as well as those bordering strongly anisotropic tissue, are misrepresented in EEG localization when neglecting the effects of white matter anisotropy [4].…”
Section: Discussionmentioning
confidence: 99%
“…following transcranial direct current stimulation) along trajectories parallel to the primary direction of the fiber tracts [4,27]. Sources located deep in the brain, as well as those bordering strongly anisotropic tissue, are misrepresented in EEG localization when neglecting the effects of white matter anisotropy [4]. One recent study that included an inverse analysis found that sulcal sources localized in EEG studies may be mislocalized outside of the sulci if white matter anisotropy is neglected [6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, when the media is anisotropic, E (r) is not necessarily in the same direction as j (r), and ρ needs to be a rank-two tensor. However, at the scalp, equation (8) is an excellent approximation to EEG, as the ρ is approximately isotropic in the tangential direction (Rush and Driscoll, 1968;Wolters et al, 2006;Petrov, 2012). meaning comes from Gauss's Law, which in its differential form given by Maxwell is written as…”
Section: Physical Interpretation Of the Surface Laplacianmentioning
confidence: 99%
“…The construction of a realistic head conductivity model requires accurate segmentation of magnetic resonance (MR) images of the head into tissue classes corresponding to different conductivity values. It is common practice to use five tissue classes-white matter (WM), gray matter (GM), cerebrospinal fluid (CSF), skull, and skin [4,5] followed by manual correction for source localization, although improvements in localization accuracy can be achieved with more classes [6]. Completely manual segmentation [7], typically performed by a clinical expert, is the gold standard.…”
Section: Introductionmentioning
confidence: 99%